2015
DOI: 10.1016/j.fsi.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Time and concentration dependency of MacroGard® induced apoptosis

Abstract: In previous studies an effect of β-glucan on apoptosis in fish was noted and in this investigation we determine the time and concentration dependency of this effect. Primary cell cultures of pronephric carp cells were incubated for 6, 24, 48 h with various concentrations ranging from 0 -1000 μg/ml of MacroGard ® β-glucan. Apoptosis was monitored via acridine orange staining. Results indicate a clear effect of time and concentration on the induction of apoptosis in vitro, with only concentration ≥ 500 μg/ml cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…For various immunostimulating substances, potential negative effects on cellular homoeostasis have been addressed (Kepka, Verburg-van Kemenade, Homa & Chadzinska, 2014;Miest & Hoole, 2015). However, PHB did not affect the expression of the studied stress-and apoptosis-related genes (cat, hsp70, hsp90; casp3, casp9).…”
Section: Discussionmentioning
confidence: 99%
“…For various immunostimulating substances, potential negative effects on cellular homoeostasis have been addressed (Kepka, Verburg-van Kemenade, Homa & Chadzinska, 2014;Miest & Hoole, 2015). However, PHB did not affect the expression of the studied stress-and apoptosis-related genes (cat, hsp70, hsp90; casp3, casp9).…”
Section: Discussionmentioning
confidence: 99%
“…Since caspase is an indicator of apoptosis [25], this result indicated that β-glucans administered as supplementary diet to honeybees do not induce apoptosis. Previous studies on apoptosis were performed on fish using 1,3 β-glucans instead of 1,3-1,6 β-glucans; those elements could be the reason for the differences on apoptosis obtained in honeybees [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…The response triggered by β-glucans can be remarkably different depending on the target organism and the dose administered [17,22]. Recent studies demonstrated that high concentration of 1,3 β-glucan is linked to the production of Reactive oxygen species (ROS) in carp leukocytes and the reduction of the immunostimulant effect inducing apoptosis in vitro and in vivo [23][24][25]. Caspase-3 (programmed cell death-activated endonuclease) is one of the key executioners of apoptosis [25].…”
Section: Introductionmentioning
confidence: 99%
“…Lower lysozyme concentrations were recorded at day 15 in fish of groups BG1-0.5 and BG2-0.5. Actually, effects of dietary β-glucan are time and dose dependent, that is, higher levels of inclusion associated to long periods of administration can actually result in reduction of immune response or even inactivation of immune system [31]. Although mechanism leading to this phenomenon are not yet clearly understood, studies have registered in vitro and in vivo leukocytes apoptosis [32] and induction of apoptosis-related genes [33] on glucan trials with fish.…”
Section: Discussionmentioning
confidence: 99%